EFFECT OF PERFORMANCE ALLOWANCES AND WORK CULTURE ON THE EMPLOYEE PERFORMANCE AT THE DIRECTORATE OF OPERATIONS OF THE NATIONAL SEARCH AND RESCUE AGENCY - Eko Bhumy Sahmalay; Lisman Manurung; Soesilo Wibowo (DIA: Jurnal Administrasi Publik, 2022)
In every organization, human resources play a very strategic and decisive role. In addition to their role as managers, human resources play determining the organization’s success in achieving its goals. This study aims to assess the effect of performance allowances and work culture on employee performance at the Directorate of Operations of the National Search and Rescue Agency. This study uses a quantitative approach. The population of this study is all civil servants (142 employees) at the Directorate of Operations of the National Search and Rescue Agency located on Jl. Angkasa Jakarta. The sampling technique uses a systematic sampling, obtaining 36 employees. Data collection of this study uses a survey method through Google Form. Data are analyzed using multiple linear, data analyses. Based on the calculation using the Ordinary Least Square method for the variables of Performance Allowance (X1), Work Culture (X2), and Employee Performance (Y), the regression equation is Y= 11.647 + 0.071 X1 + 0.465 X2. The study results show that the performance allowance, work culture, and employee performance simultaneously had a significant effect on the employee performance at the Directorate of Operations of the National Search and Rescue Agency. The multiple regression results show that the regression coefficient of the Performance Allowance and Work Culture variables proves that there was a positive effect on employee performance. Thus, it can be concluded that the Performance Allowance and Work Culture variables together have a significant effect on the Employee Performance at the Directorate of Operations of the National Search and Rescue Agency. Therefore, the better the Performance Allowance and Work Culture, the higher the Employee Performance at the Directorate of Operations of the National Search and Rescue Agency. Furthermore, the organization’s core values ​​should be stated in standard operating procedures in activities/tasks to improve work culture and employee performance.